Clinical Autonomic Dysfunction : Measurement, Indications, Therapies, and Outcomes - Colombo, Joseph; Arora, Rohit; DePace, Nicholas L.; Vinik, Aaron I. (Springer International Publishing : Imprint: Springer, 2015)
This book presents the concepts underlying the measurement of parasympathetic and sympathetic (P&S) activity in the autonomic nervous system and the application of these measurements in the development of therapeutic guidelines for treating dysfunctions in these processes. It provides an overview of the anatomy, physiology, and biochemistry of the autonomic nervous system; details general clinical applications of P&S monitoring that are independent of specialty or disease; presents the pathophysiology of P&S dysfunction in specific disorders, expected test results, therapeutic options, and expected outcomes; and includes case studies and longitudinal studies that demonstrate the major concepts for the common diseases for which P&S monitoring is recommended. Clinical Autonomic Dysfunction enables clinicians to improve patient outcomes by identifying and treating clinical problems related to autonomic nervous system disorders.